Leucoagaricus rosuliformis sp. nov. (Agaricales, Basidiomycota) from Changa Manga Forest, Punjab, Pakistan - Jabeen, Sana; Naseer, Arooj; Ijaz, Hira; Tuba; Yasmeen, Aneela; Niazi, Abdul Rehman; Zhao, Chang-Lin (Phytotaxa, 2024)
Leucoagaricus rosuliformis is described as a new species from the Changa Manga Forest, Punjab, Pakistan. This species can be separated from its close relatives, L. lahorensis and L. changamangaensis by its rosette-like central disc and with dense squamules becoming scattered towards margins. Molecular phylogenetic analyses using nuclear ribosomal DNA sequences from the internal transcribed spacer region also supported this taxon as a distinct species.